Tax Risk Assessment and Assurance Reform in Response to the Digitalised Economy - Strauss, Helena; Fawcett, Tyson; Schutte, Danie (Journal of Telecommunications and the Digital Economy, 2020)
The digitalisation of the economy has increased tax administrations’ traditional tax risks and introduced new tax non-compliance risks, such as the use of income suppression software and tax fraud associated with the use of alternative payment methods, such as cryptocurrencies. This study focuses on the global reform that took place among tax authorities from a tax risk management and assurance perspective. The study was executed in two phases, including a cross-national literature review to synthesise international reform regarding tax risk management and assurance in response to the digitalisation of the economy. This process was followed by interviews with risk, technology and data experts of 30 global tax authorities in order to evaluate the level of implementation of the global reform measures identified in the first research phase. The research results suggest an imbalance in reform among participants from developed and developing economies. An inability to optimise tax risk and assurance management within the digitalised economy will negatively impact the tax authorities’ ability to maximise tax collection within the digitalised economy. This is especially concerning if the significant role of digital platforms on future global economic value creation is considered.